Comparison of cardiac image-derived input functions for quantitative whole body [18F]FDG imaging with arterial blood sampling - Reed, Murray Bruce; Godbersen, Godber Mathis; Vraka, Chrysoula; Rausch, Ivo; Ponce de León, Magdalena; Popper, Valentin; Geist, Barbara; Nics, Lukas; Komorowski, Arkadiusz; Karanikas, Georgios; Beyer, Thomas; Traub-Weidinger, Tatjana; et al. (Frontiers in Physiology, 2023)
Dynamic positron emission tomography (PET) and the application of kinetic models can provide important quantitative information based on its temporal information. This however requires arterial blood sampling, which can be challenging to acquire. Nowadays, state-of-the-art PET/CT systems offer fully-automated, whole-body (WB) kinetic modelling protocols using image-derived input functions (IDIF) to replace arterial blood sampling. Here, we compared the validity of an automatic WB kinetic model protocol to the reference standard arterial input function (AIF) for both clinical and research settings. Sixteen healthy participants underwent dynamic WB [18F]FDG scans using a continuous bed motion PET/CT system with simultaneous arterial blood sampling. Multiple processing pipelines that included automatic and manually generated IDIFs derived from the aorta and left ventricle, with and without motion correction were compared to the AIF. Subsequently generated quantitative images of glucose metabolism were compared to evaluate performance of the different input functions. We observed moderate to high correlations between IDIFs and the AIF regarding area under the curve (r=0.49 – 0.89) as well as for the cerebral metabolic rate of glucose (CMRGlu) (r = 0.68 – 0.95). Manual placing of IDIFs and motion correction further improved their similarity to the AIF. In general, the automatic vendor protocol is a feasible approach for the quantification of CMRGlu for both, clinical and research settings where expertise or time is not available. However, we advise on a rigorous inspection of the placement of the volume of interest, the resulting IDIF, and the quantitative values to ensure valid interpretations. In protocols requiring longer scan times or where cohorts are prone to involuntary movement, manual IDIF definition with additional motion correction is recommended, as this has greater accuracy and reliability.